Determinantes de la intención de contratar un BPO contable o financiero por empresas en Lima - Campo Meza, Patricia Christins (2023)
Although business process outsourcing (BPO) is spreading widely nowadays to decrease certain associated costs in companies, there are many risks associated with these projects that affect the effectiveness of the results. This research evaluated the impacts of: confidence in hiring, outsourcing-related costs, level of specialization, quality improvement, strategic risk, information for decision making, behavioral uncertainty, and intention to outsource on the intention to outsource. In order to test the hypotheses, we used data collected from 103 companies through surveys conducted in the city of Lima-Peru, during the period December 2021 to March 2022. The PLS-SEM analysis method was used with these data. The results confirm that in Peruvian companies in Lima, strategic risk and behavioral uncertainty determine the decision to outsource or BPO. Interestingly, the hypothesis of specialization that generates economies of scale and the low costs offered by specialized companies have not been valued by the companies surveyed in this study.